Using Personality Type Preferences to Enhance Team Work in Extension Programs - J. Brianne Bird; Alexa J. Lamm; Hannah Carter (EDIS)
This 4-page fact sheet is the fifth of the Teaching to Personality Types series, a series on teaching different personality types. It covers the practical ways in which Extension professionals can use the influence of personality type preferences to enhance team dynamics in Extension program development and implementation. It also covers the Myers-Briggs personality type indicator, True Colors personality type indicator, and the Kirton Adaption Innovation Inventory. Written by J. Brianne Bird, Alexa J. Lamm, and Hannah Carter, and published by the Department of Agricultural Education and Communication, September 2016.